THE ETHICAL DIMENSIONS OF REWARD-DRIVEN INFORMATION REPORTING - Zhang, Wei (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2024)
Online bounty reporting behavior represents a complex phenomenon emerging within the digital realm, encompassing various information-related actions like human flesh searches, online surveillance, whistleblowing, seeking assistance, and asserting rights. Rooted in a collective moral critique framework, this behavior integrates economic incentives with information-sharing capabilities afforded by cyberspace, encouraging individuals to track, disclose, and take "defensive actions" against acquaintances, culminating in a distinct form of online reporting. This study delves into the intricacies of this behavior, shedding light on its evolution and characteristics within the contemporary digital landscape